PENGARUH PENGENDALIAN INTERN TERHADAP AKUNTABILITAS MANAJEMEN KEUANGAN SEKOLAH - Kartikawati Kartikawati (Universitas PGRI Madiun, 2016)
This study aims to determine controlling effect intern (control environment, risk assessment, control activities, information and communication, and monitoring) on accountability financial management school. This study also uses control variable which is a measure of school and school status. This study uses census. Tests conducted on 98 bendahara primary and secondary schools are elementary, junior high, high school, and p private SMK Madiun city. Data collection using questionnaire and test analysis using multiple linear regression and statistical analysis diskriptif. Result research shows that the internal control element of evaluation risk, control activities, monitoring, school size and school status have an influence on financial manajement school accountability. Instead the control environment and information and communication has no effect. However jointly affect the internal control of financial management accountability for 85.8% of the school.